Planning informality: promoting a market of planned informal settlements - Fort, Ricardo (2018)
About 30% of the population in developing countries live in informal urban settlements lacking adequate basic services, public spaces and urban equipment. The origin to most of these shortcomings can be traced to a single feature: the urban layout design.